Knowledge of Sports Injury Management in the North Sumatra National Paralympic Committee Coach - Ika Endah Puspita Sari; Liliana Puspa Sari; Khairul Usman (Jurnal Pendidikan Jasmani (JPJ), 2020)
The purpose of this study was to determine the knowledge of handling sports injuries in the North Sumatra National Paralympic Committee (NPC) trainer. This research was conducted on Sunday, February 14, 2018 at the NPC Secretariat of North Sumatra Province Jl. The 22 nd Example Stadium Medan. The method used in this study is a descriptive descriptive method with the distribution of questionnaires as an instrument to obtain research data. Many of the population in this study were all North Sumatra National Paralympic Committee (NPC) trainers, amounting to 8 people, while the sample used was total sampling, meaning 8 people. The results of the study found that 3 responses (37.50%) had knowledge of handling sports injuries is classified as good, 5 respondents (62.50%) have knowledge of handling sports injuries that are classified as moderate. Based on the results of the calculation of the average score of knowledge about handling sports injuries that is equal to 56%, it can be concluded that the level of knowledge of handling sports injuries on the North Sumatra National Paralympic Committee (NPC) is classified as Medium.